Pre-teaching to enhance inclusive learning: connecting cognition, motivation, volition, and emotion - Blanc, Barbara; Aydan, Seda; Mamas, Christoforos (Frontiers in Education, 2025)
Some learners face systemic or personal barriers to participate in classroom activities, such as limited access to high-quality educational resources, language challenges, varying levels of prior knowledge, or individual learning needs and abilities. Pre-teaching can help students overcome these challenges. This conceptual paper presents pre-teaching as an adaptive teaching method and propose the INVO model as a theoretical framework for pre-teaching, which has not yet been comprehensively developed, and considers the cognitive as well as the motivational-volitional, and emotional dimensions of learning. The paper outlines vocabulary preparation, cognitive activation, culturally sensitive teaching, and research-based learning as possible implementations of pre-teaching, demonstrating how this prepares students for upcoming subject matter, not only to improve academic performance but also to promote self-efficacy, emotional readiness to learn and contribute to more inclusive and differentiated learning environments in the long term. Methodologically robust studies are needed to empirically test the effectiveness of this teaching method for fostering the acquisition of subject-specific and interdisciplinary competencies and to demonstrate its practical relevance for inclusive learning.